Antibacterial And Antifungal Activity Of Various Whole Plant Extracts Of Aerva Tomentosa Forsk. (Amaranthaceae) - ASHISH SETHI; R. A. SHARMA (International Journal of Pharma and Bio Sciences, 2011)
The antimicrobial activity of ethanol, petroleum ether, dichloromethane, ethyl acetate, methanol and aqueous whole plant extracts of Aerva tomentosa (Amaranthaceae) were tested against nine human pathogens such as Bacillus subtilis, Enterobactor aerogenes, Escherichia coli and Pseudomonas aeruginosa bacterias and Aspergillus flavus, Aspergillus niger, Candida albicans, Trichophyton rubrum and Penicillium crysogenum fungus by using agar well diffusion method. Among the six extracts the aqueous cold extract of Aerva tomentosa showed the highest range of activity against all tested human pathogens. E. aerogenes, E. coli, A. niger, C. albicans, T. rubrum and P. crysogenum were found to be susceptible forming highest zone of inhibition diameter of 12-20 mm at concentration of 4 mg/ml, suggesting that Aerva tomentosa was strongly inhibitory towards these organisms. Appreciable activity against A. niger was exhibited by both cold extracts of aqueous and ethyl acetate (IZ 20.00±0.00 mm and17.30±0.33 mm, respectively). These results indicate that Aerva tomentosa (Amaranthaceae) possessed potential Antibacterial and Antifungal activities.